Physical exercise and social media addiction among adolescents: a chain mediation analysis of cognitive flexibility and negative attention bias - Jie Luo; Shiqi Long; Yuhan Chen; Mengting Pan; Yang Liu; Xiaodi Ma; Jianzhang Luo (Frontiers in Psychiatry, 2026)
Background and objectives Physical Exercise (PE) is associated with multiple aspects of adolescent psychological and cognitive functioning. Cognitive Flexibility (CF) and Negative attention bias (NAB) may help explain the association between PE and Social Media Addiction (SMA), yet their joint indirect roles remain insufficiently examined. This study tested a cross-sectional serial indirect-effects model linking PE, CF, NAB, and SMA among Chinese adolescents. Methods A self-reported survey was conducted among 3,375 adolescents in China, collecting data on PE, SMA, CF, NAB, and demographic variables. As an initial step, descriptive statistics and correlation analyses were conducted to examine PE, SMA, CF, and NAB. A chain mediation model was subsequently established to investigate whether CF and NAB sequentially mediated the association between PE and SMA. Results The correlation analysis revealed that PE was significantly and negatively associated with both SMA and NAB, while exhibiting a significant positive association with CF. After incorporating CF into the model, the negative correlation between PE and SMA weakened but remained significant. In addition, CF was significantly and negatively associated with SMA, providing preliminary support for its potential mediating role in the association between PE and SMA. CF was also significantly and negatively related to NAB, whereas NAB exhibited a significant positive association with SMA. These results indicate that CF may function as an important intermediary mechanism linking PE to lower levels of SMA, potentially through its influence on NAB. Conclusion PE was associated with lower levels of SMA both directly and indirectly, with the indirect effect operating through increased CF and reduced NAB. This serial mediation mechanism provides a more comprehensive understanding of how PE may influence adolescent mental health. The findings further highlight the potential value of PE as a preventive and intervention-oriented strategy for reducing SMA among adolescents. It is recommended that promoting PE could enhance CF and improve attention biases, thereby effectively mitigating the risk of SMA.